Pedagogies for the Future Leading Quality Learning and Teaching in Higher Education - Brandenburg, Robyn. (SensePublishers : Imprint: SensePublishers, 2013)
Pedagogies for the Future illustrates a unique and exciting endeavor whereby a group of academics across one university developed a professional learning community for the purposes of investigating, articulating and developing their scholarship of practice. Through their collaborative efforts, these educator-researchers sit at the forefront of calls to take teaching seriously in higher education and to recognize the powerful potential of interdisciplinary collaboration. The book provides a model for establishing learning communities in higher education and demonstrates that such work is not only possible but also successful. From vision to reality, Pedagogies for the Future offers important insights into the complex nature of researching teaching and learning in higher education from the perspectives of those directly engaged in it. This book will be of great interest and value to both scholars and administrators. Associate Professor Amanda Berry Leiden University, The Netherlands Pedagogies for the Future is an ambitious but critically important work & This book reminds us of the complex interactions between culture and pedagogy and the importance of paying the closest possible attention to the effects of how we teach and how well our students learn. Professor Tom Russell Queens University, Canada